PENGARUH KESENIAN TARI GANDRUNG SEBAGAI SARANA PERKEMBANGAN BAKAT PERSERTA DIDIK SMP DI KABUPATEN BANYUWANGI - Ivan Rizki Fauzi; Gesta Pramatasari; Kharisma Husnul Khotimah; Najma Fatimatuz Zakiyah; Firdha Yusmar; I Ketut Mahardika; Rizka Elan Fadilah (Pendidikan Fisika FKIP UNEJ, 2022)
The purpose of this study is to describe the Gandrung Dance in the City Banyuwangi, East Java Province, to make it easier for students to develop talents the art of Gandrung Dance and can be a medium of learning for all. Method research that is used as a background, the history of the development of Gandrung art, and the form of presentation in Banyuwangi Regency using descriptive methods qualitative. Gandrung dance itself is a dance performed by adults, you can too delivered by junior high school students in Banyuwangi Regency. This dance performed solo or in groups. There are three types of Jejer Gandrung dance Floor patterns include circles, squares, and lines. In the Jejer Gandrung Kembang dance Menur there are four floor patterns including: Trapezoid, circle, straight line, and arch. Likewise, the Gandrung Dor dance has seven floor patterns including lines curve, straight line, rhombus, trapezoid, parallelogram, and circle.